2010
DOI: 10.1021/jp1022357
|View full text |Cite
|
Sign up to set email alerts
|

Na+ and Ca2+ Effect on the Hydration and Orientation of the Phosphate Group of DPPC at AirWater and AirHydrated Silica Interfaces

Abstract: Hydration and orientation of the phosphate group of dipalmitoylphosphatidylcholine (DPPC) monolayers in the liquid-expanded (LE) phase and the liquid-condensed (LC) phase in the presence of sodium ions and calcium ions was investigated with vibrational sum frequency generation (SFG) spectroscopy at the airaqueous interface in conjunction with surface pressure measurements. In the LE phase, both sodium and calcium affect the phosphate group hydration. In the LC phase, however, sodium ions affect the phosphate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
115
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 98 publications
17
115
1
Order By: Relevance
“…When it is fully dehydrated (CWT = 0), Na + can be bound to at most 7 lipid oxygens. Between these two extreme cases, Na + is bound to oxygens [2,6] with the total coordination number (CLP+CWT)∈ [5,7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When it is fully dehydrated (CWT = 0), Na + can be bound to at most 7 lipid oxygens. Between these two extreme cases, Na + is bound to oxygens [2,6] with the total coordination number (CLP+CWT)∈ [5,7].…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] While bound to membranes in aqueous solution, a hydrated metal cation will lose one or more water molecules from its first hydration shell, resulting in several possible bound configurations. 9,10 Although the binding constant and…”
mentioning
confidence: 99%
“…Therefore, a bound state can be characterized by the ion's coordination number with lipid binding sites and its simultaneous coordination number with water molecules. A number of experiments [3][4][5][6] and simulation works [6][7][8][9][10][11][12][13] have indicated that metal cations bind directly to the oxygen atoms of the negative charged phosphate (PO − 4 ) and carbonyl (C=O) groups of lipid molecules. Accordingly, we defined two collective variables (CVs) to describe the ion's bound states: the coordination number between a Na + ion and lipid (including cholesterol) oxygens (CLP), and the coordination number between a Na + ion and water oxygens (CWT).…”
Section: Collective Variablesmentioning
confidence: 99%
“…Several experiments revealed that metal cations are bound to the negative charged head groups of phospholipid membranes [3][4][5][6] . Meanwhile, numerous molecular dynamics (MD) simulations have been performed to study the binding of metal cations at phospholipid membranes from an atomic point of view [6][7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the replacement of a pure water subphase with inorganic salt solutions causes alterations in the phase behavior of the monolayer, especially for FAs and phospholipids [31][32][33][34][35][36][37]. The effect of Ca 2+ has been widely investigated due to its relevance in biological membranes [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%